Attitudes of mothers attending public hospitals in Addis Ababa, Ethiopia, to neonatal sunlight exposure: a cross-sectional study. Issue 1 (7th September 2022) - Ashebir, Yohannes Godie; Sebsibe, Girum Teshome; Gela, Debela; Kebede, Mekonen Adimasu
Abstract : Background: Sunlight exposure helps the body produce vitamin D, prevents rickets and is used for neonatal jaundice treatment. Good neonatal sunlight exposure is exposing the neonate to sunlight in the morning, 8:00 to 10:00, for 30 to 60 min. However, little is known about the practice of neonatal sunlight exposure among mothers in Ethiopia. This study aimed to assess the practices and factors associated with neonatal sunlight exposure among mothers attending public hospitals in Addis Ababa, Ethiopia. Methods: An institution-based cross-sectional study was conducted among 420 mothers attending public hospitals in Addis Ababa. Study participants were selected using a systematic random sampling method. The collected data were entered into Epi-data V.4.6 and exported to SPSS V.26 for analysis. Descriptive and logistic regression analyses were conducted. Results: The practice of neonatal sunlight exposure among mothers was 27.1%. Neonatal age of 16–28 days (adjusted OR (aOR) 1.99, 95% CI 1.15 to 3.44), family members of 4–6 (aOR 1.86, 95% CI 1.08 to 3.21) and ≥7 (aOR 4.43, 95% CI 1.54 to 12.78), living in compound/villa houses (aOR 2.59, 95% CI 1.26 to 5.33), complete antenatal care (ANC) follow-up (aOR 2.79, 95% CI 1.49 to 5.22), delivery at term (aOR 2.54, 95% CI 1.06 to 6.07), poor knowledge of sunlight exposure (aOR 0.40, 95% CI 0.23 to 0.71) and no fear of sunlight exposure (aOR 1.83, 95% CI 1.08 to 3.12) were factors associated with the practice of neonatal sunlight exposure. Conclusion: This study revealed that 27.1% of mothers had good sunlight exposure. Advanced neonatal age, larger family, living in compound/villa houses, complete ANC visits and term delivery were associated with good practices, whereas poor knowledge and fear of sunlight exposure were associated with poor practices. Therefore, interventions focusing on these findings are required to improve the practice of neonatal sunlight exposure.